厦门滨海湿地冬季鸟类群落多样性研究 - 方文珍; 陈志鸿; 陈小麟; 林清贤 (2007)
1999年12月~2000年2月对厦门滨海湿地12个样区冬季鸟类的种类和数量进行调查。并选取调查地的7个参数定量分析滨海湿地鸟类群落多样性的主要影响因子。结果显示,厦门冬季滨海湿地鸟类共有15科45种。其中,风头潜鸭(Aythya fuligula)、红嘴鸥(Larus ridibundus)、黑腹滨鹬(Calidris alpina)和白鹭(Egretta garzetta)为优势种,其数量之和占总数量的76%。白鹭为厦门湿地的广布种,在12个样区均有分布。厦门冬季湿地鸟类群落的相似性与其滩涂底质的相似性之间存在一定的相关。湿地鸟类群落多样性的主要影响因素包括湿地周边建筑物、交通干扰、人工水产养殖场和周边陆地植被覆盖状况等。湿地鸟类的种群密度则受水域含盐量、交通干扰的显著影响。 The bird species and their relative abundance were investigated on the twelve quadrats in Xiamen wetlands from December 1999 to February 2000.Seven environmental parameters were selected for analyzing the main impact factors on the bird community diversity of this area.The results showed that there were 15 families and 45 species of birds found in Xiamen wetlands during the research period.The dominant species were Tufted Duck(Aythya fuligula),Black-headed Gull(Larus ridibundus),Dunlin(Calidris alpina) and Little Egret(Egretta garzetta),and the individual number of these 4 species occupied 76% of the total individual number.Little Egret was the commonest bird,which distributed in every quadrat of the area.There is a relationship between the similarities of bird communities and the similarities of sediment types of wetland.The factors mainly influencing the bird community diversity are artificial building,traffic disturbance,aquiculture and terrestrial vegetation,and those highly influencing the population density of wetland bird are the water salinity and traffic disturbance. 福建省自然科学基金资助项目(D9910003);; 厦门市环境保护科研所资助项目